Genomic Indexing by Somatic Gene Recombination of mRNA/ncRNA – Does It Play a Role in Genomic Mosaicism, Memory Formation, and Alzheimer’s Disease? - Ueberham, Uwe; Arendt, Thomas (Frontiers in Genetics, 2020)
Recent evidence indicates that genomic individuality of neurons, characterized by DNA-content variation, is a common if not universal phenomenon in the human brain that that occurs naturally but also can show aberrancies that had been linked to the pathomechanism of Alzheimer´s disease and related neurodegenerative disorders. Etiologically, this genomic mosaic was suggested to arise from defects of cell cycle regulation that may occur either during brain development or in the mature brain after terminal differentiation of neurons. Here, we want to draw the attention towards another mechanism that can give rise to genomic individuality of neurons with far-reaching consequences that has its origin in the transcriptome rather than in replication defects of the genome, i.e. somatic gene recombination of RNA. We continue to develop the concept that somatic gene recombination of RNA provides a physiological process that through integration of intronless mRNA/ncRNA into the genome allows to index a particular functional state at the level of the individual neuron. By insertion of defined RNAs in a somatic recombination process, the presence of specific mRNA transcripts within a definite temporal context can be ‘frozen’ and serve as an index that can be recalled at any later point of time. This allows fixing information related to a specific neuronal state of differentiation and/or activity relevant to a memory trace. We suggest, this process is used throughout the lifetime of each neuron and might have both advantageous and deleterious consequences.